PENERAPAN MEDIA PEMBELAJARAN DIORAMA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATER SIKLUS AIR KELAS IV SD TIGA PUTRA KOTA KUPANG - Sofia Godeliva Un Lala; Geraldeen Bali Dendo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The formulation of the problem in this study is "How to improve student learning outcomes on water cycle material through class IV diorama learning media SD Tiga Putra Kupang". The purpose of this study was to determine efforts to improve learning outcomes through diorama learning media in grade IV students of SD Tiga Putra Kupang. This type of research is Classroom Action Research with data analysis techniques, namely qualitative descriptive with percentages based on data that has been collected and then categorized into a set formulation. The subjects of the study were grade IV students which amounted to 13 students. Data collection techniques use observation, tests and documentation studies. The research instruments used in this study were teacher and student observation sheets, tests and documentation studies. The results of research conducted showed that in cycles I and II teacher observations made by observers I and II it was known that there was 1 aspect that had not been done, namely the balum variety in providing examples on water cycle material, while in cycle II the results of observations made by observers I and II were the implementation of all specified aspects and the completeness of the percentage of learning completeness in cycle I of 54% with a value of 63.84 categories are sufficient while in cycle II there was an increase with a percentage of 100% with an average value of 85.07. The application of diorama learning media can effectively improve student learning outcomes at SD Tiga Putra Kupang.